Anatomy of grand corruption: A composite corruption risk index based on objective data - Mihály Fazekas; István János Tóth; Lawrence Peter King (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
Although both the academic and policy communities have attached great importance to measuring corruption, most of the currently available measures are biased and too broad to test theory or guide policy. This article proposes a new composite indicator of grand corruption based on a wide range of elementary indicators. These indicators are derived from a rich qualitative evidence on public procurement corruption and a statistical analysis of a public procurement data in Hungary. The composite indicator is constructed by linking public procurement process 'red flags' to restrictions of market access. This method utilizes administrative data that is available in practically every developed country and avoids the pitfalls both of perception based indicators and previous 'objective' measures of corruption. It creates an estimation of institutionalised grand corruption that is consistent over time and across countries. The composite indicator is validated using company profitability and political connections data.
Keywords: D72; D73; H57; 330; public procurement; grand corruption; corruption technique; composite corruption risk index